The Effects of the Sports Sponsorship on the Formation of Grab Corporate Image After 18th Asian Games - Zulfikri Zulfikri; Didik Susetyo; Bayu Hardiyono (Jurusan Manajemen Fakultas Ekonomi Universitas Sriwijaya, 2021)
The purpose of this study was to study the effect of the sport's sponsors on the corporate image formation of the Grab after the 18th Asian Games. The data used in this study were primary data obtained from questionnaire questionnaires that had been distributed to the intended respondents as community users of Grab in the City of Palembang. This study uses a simple linear regression analysis technique. The results of this study indicate that sports sponsorship has a significant influence in shaping the corporate image of Grab after the 2018 Asian Games with sig. t of (a) = 0,000 <0.05 or 5%, so Ho is rejected and Ha is accepted. This means that an increase in sports sponsorships will improve Grab's corporate image, and vice versa if there is a decrease in sports sponsors the Grab's corporate image will also increase.